The relationship between dysfunctional attitudes, rumination response styles and depression - (:unkn) unknown (Kare Publishing, 2013)
The relationship between dysfunctional attitudes, rumination response styles and depression Objective: In our study we aimed to investigate the relationship between rumination response styles, dysfunctional attitudes and depression. Methods: 60 patients diagnosed with depression according to the DSM-IV-TR diagnostic criteria in the Bakirkoy Training and Research Hospital for Psychiatry, Neurology and Neurosurgery outpatient clinics are involved in our study. All participants were administered a sociodemographic questionnaire, the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), Beck Depression Inventory (BDI), Dysfunctional Attitude Scale (DAS) and Ruminative Responses Scale (RRS-short version). Results: In our study, there was mild-moderate negative correlation between depression and the perfectionist attitudes, need for approval, independent attitudes subscores. The RRS-short version brooding subscore was highly positively correlated with depression. Depression and RRS-short version reflecting score was moderately and positively correlated. As predictors of depression, high subscores of RRS-short version brooding and RRS-short version reflected increased risk for depression, whereas high subscores of DAS perfectionist attitudes are evaluated to be protective for depression. Conclusions: In our study, in contrast to the literature, it was shown that dysfunctional attitudes are not positively correlated with depression nor are they predictors of depression. However, it may not be appropriate to make such comment based on a single study. Factors that can lead to this conclusion are discussed in the study. On the other hand, our study emphasizes the key role of rumination in depression. In practice of cognitive behavioral therapy of which efficacy in treatment of patients with depression has been know, assessment of ruminative responses, treatment techniques for reducing ruminative responses should be targeted.
Keywords: Brooding; Depression; Dysfunctional attitudes; Reflecting; Rumination